The Science of Emotional Intelligence 2021
DOI: 10.5772/intechopen.98229
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Develop Emotional Intelligence in Early Childhood

Abstract: Children have many opportunities in early childhood education that support their emotions. These opportunities need to be transformed into learning situations appropriate to their development and developed. Learnings cannot happen independently of emotional intelligence. Social–emotional skills must be developed in education to achieve both academic success and success in life. It is important to support emotional intelligence in early childhood education to enable children to be emotionally healthy, to cope w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In the future, researchers could include information related to emotional intelligence into the curriculum and textbooks to convey knowledge of correct emotional understanding. Social-emotional skills must be developed to achieve academic success (Ulutaş et al, 2021). Results confirmed that teachers struggle with circumstances in the domain of social and emotional issues and teachers need to include emotional intelligence competencies in the curriculum (Hadar et al, 2020).…”
Section: Prospects For Further Researchmentioning
confidence: 80%
See 4 more Smart Citations
“…In the future, researchers could include information related to emotional intelligence into the curriculum and textbooks to convey knowledge of correct emotional understanding. Social-emotional skills must be developed to achieve academic success (Ulutaş et al, 2021). Results confirmed that teachers struggle with circumstances in the domain of social and emotional issues and teachers need to include emotional intelligence competencies in the curriculum (Hadar et al, 2020).…”
Section: Prospects For Further Researchmentioning
confidence: 80%
“…Responsible students ease the workload and reduce teachers' burnout when classrooms are peaceful, and all the work completed as required with social and emotional support. Teachers who train children emotional intelligence contingencies manage their emotions better, resort to less aggression, have more positive general moods, are more successful academically, move away from negative habits, establish positive social relationships with their family, peers, and social circles, and show social adaptation (Ulutaş et al, 2021). Significant improvement of students' behavior demonstrated a positive impact after EI training.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations